Discharge disposition and clinical outcomes of patients hospitalized with COVID-19. (May 2023) - Patel, Shiv; Truong, Gia Thinh; Rajan, Ajay; Creech, Zachary; Walters, Ryan; Ng, Ian; Destache, Christopher; Vivekanandan, Renuga; Tierney, Maureen; Velagapudi, Manasa
Highlights: A total of 65.2% of patients hospitalized for COVID-19 were discharged home. Younger age and shorter length of stay were predictors of discharge to home. Male gender, Hispanic ethnicity, and invasive ventilation are associated with lower odds of discharge to home. Discharge home is associated with lower all-cause mortality rates after hospitalization. Patients discharged home had longer survival compared to those who were not. Abstract: Objectives: By better understanding the long-term effects of COVID-19 and assessing rehabilitation placement among the patients in our study, we hope to determine the predictors of rehabilitation needs in individuals suffering from the long-term sequelae of COVID-19. Methods: A retrospective chart review was performed of adult patients with a positive COVID-19 polymerase chain reaction test among multiple hospitals in a regional health system. The main outcomes measured were discharge disposition, total length of hospital stay, and overall all-cause mortality and readmission rates within 30 and 90 days of discharge. Results: Of the 2502 patients included in the study, we found that 65.2% were discharged to home, while the remaining patients were discharged to home healthcare (33.6%), skilled nursing facilities (31.7%), or long-term acute rehabilitation centers (11.6%). The overall all-cause mortality rate at 30 and 90 days were 2.7% and 4.4%, respectively. The overall all-cause 30-day and 90-day readmission rates were 7.0% and 7.6%, respectively. Conclusion: Younger age and shorter hospitalization stays were the most important predictors of home discharge. Discharge to home was also significantly associated with lower all-cause mortality rates at 30 and 90 days after discharge.